The Ethical Challenges of Gamification in Iran: Uncovering the Dark Side - Mona Jami Pour; Hamideh Binaei (‫مدیریت بازرگانی)
ObjectiveThe popularity of gamification in business, in areas such as marketing, sales, human resources, and education is growing rapidly. Gamification has also attracted significant attention from academic researchers as an emerging study field. It is used as a new approach to reinforce desirable behaviors in employees, increase customer engagement with company products, and even change citizens' perceptions of their environment. Predictions indicate a growing trend of investment in this study field at both business and societal levels. Despite the undeniable advantages of gamification in businesses and its impact on individuals and societies, its implementation is accompanied by a wide range of challenges. There have been limited studies addressing its ethical aspects in Iran; therefore, the present study aims to identify and prioritize the ethical challenges of gamification in Iran to improve the design and application of gamification by understanding its dark aspects. MethodologyTo achieve the research objective, a sequential exploratory mixed-methods approach was employed. In the first stage, a qualitative approach was used, conducting 15 semi-structured interviews to identify and extract the ethical challenges of gamification. The qualitative data obtained from this stage were analyzed using thematic analysis. In the second stage, a quantitative approach, specifically Shannon's entropy method, was utilized to rank and prioritize the ethical challenges of gamification. The statistical population of this research consisted of academic experts, specialists, designers, and researchers active in the field of gamification, who were selected and invited to participate using a judgmental sampling method.   FindingsThe analysis of the interviews with experts revealed that the ethical challenges of gamification in Iran could be categorized into seven main categories and 45 indicators. The extracted categories, in order of priority, include negative mental and physical consequences, access-related challenges, security and privacy challenges, content-related challenges, challenges related to the quality and accuracy of information (information pollution), challenges related to intellectual property rights, and challenges of responsibility and accountability. ConclusionA review of studies on gamification reveals that most research has focused on the benefits and positive outcomes of this emerging trend, with fewer studies addressing its ethical issues and negative aspects. This study identifies and prioritizes a set of ethical challenges of gamification to provide a holistic understanding of the darker aspects of implementing this novel approach within the cultural, social, and religious context of Iran. Given the increasing penetration of gamification in various aspects of business and society, the results of this research will assist developers of gamification programs and policymakers in this field. It will help them mitigate the negative consequences by providing comprehensive insights into the ethical challenges and dark sides of gamification at both the business and societal levels. Additionally, this research will help create a safer environment for participants in gamified programs. It will also offer users insights to reduce their vulnerability to these programs.